Physical and physiological corn seed quality during processing (Revista de Ciências Agroveterinárias, 2015)
The aim of this study was to assess the effect of the processing phases on the physical and physiological quality of seeds of two Creole genotypes and two varieties of open pollinated corn, as well as test the processing efficiency of the system. The seeds were collected at the reception, after pre-cleaning, the drying process, size and density classification, and storage. The seeds were evaluated for the moisture content, physical purity, germination, germination index, accelerated aging, cold test, tetrazolium, electrical conductivity, and seedling and radicle length. The processing enhanced the seed quality, and higher performance was observed for the analyzed parameters during storage. The Creole genotypes were more tolerant to processing and showed higher physical and physiological seed quality.
Keywords: Seed; Vigor; Viability; Cold test; Tetrazolium.